RECEPTION OF THE HOLY SCRIPTURES IN PSELLOS’S IMPERIAL ORATIONS DEDICATED TO ROMANOS IV DIOGENES - JASMINA ŠARANAC STAMENKOVIĆ (Истраживања)
This study analyzes the biblical motifs used by Michael Psellos, one of the most learned figures of the eleventh-century Constantinople intellectual elite, as prototexts for his imperial orations dedicated to Emperor Romanos IV Diogenes. A comparative analysis of his imperial orations and the Holy Scriptures reveals Psellos’s exceptional knowledge of the Bible. Through biblical motifs, Psellos affirmed the Byzantine imperial ideology in practice, which held that the Byzantine emperor was God’s emissary on Earth.